Audit Report Lag in High and Low Risk Manufacturing Firms - Muhamad Rafli; Dirvi Surya Abbas (urn:nbn:id:umrah-jafi.v9i1.2025.001jiafi.v9i2, 2025)
This study examines the influence of audit fee, audit tenure, inherent risk, key audit matters, auditor switching, and audit committee meeting frequency on audit report lag (ARL). The sample is divided into high- and low-inherent-risk groups to explore potential differences. A quantitative approach using panel data regression is applied to manufacturing firms listed on the Indonesia Stock Exchange during 2022–2024. The Fixed Effect Model (FEM) is used for the overall sample, while the Random Effect Model (REM) is applied to the subsamples. The findings show that audit tenure, inherent risk, and auditor switching significantly reduce ARL. Audit fee has a positive but insignificant effect, while key audit matters and audit committee activity are not significant. Further analysis indicates differing patterns across risk groups. In low-risk firms, only audit fee significantly decreases ARL. In contrast, for high-risk firms, inherent risk and key audit matters are the only significant factors, although the overall model is not statistically significant. These results suggest that the determinants of ARL depend on contextual conditions, and commonly used variables may not sufficiently explain audit timeliness in high-risk corporate settings.